A night low‐illumination image enhancement model based on small probability area filtering and lossless mapping enhancement. Issue 13 (29th July 2021) - He, Lei; Long, Wei; Liu, Shouxin; Li, Yanyan; Ding, Wei
Abstract: A novel night‐time image enhancement approach was proposed in this paper to address the problems of low contrast and poor details of low‐illumination images captured at night. To begin with, the luminance component V was extracted that was irrelevant to the colour information of the image upon converting the image to the HSV space from the RGB space. Then, by converting the luminance component V of the image into the probability space, the image was divided into a small‐probability grey‐scale area and a normal area based on the theory of probability. Moreover, pixels were transferred from the small probability area to the normal area of the image according to the nearest attribution principle that was established. Lastly, the contrast enhancement of the image was realized thanks to lossless mapping functions without losing the number of grey levels of the image. As can be observed from experimental results, the proposed method is superior to the most advanced algorithm in visual quality and quantitative measurement.